The Productivity of Lumbricus rubellus Earthworms in Cow Manure Media with the Addition of Cricket Manure - T. P. Utami; A. M. Fuah; V. A. Mendrofa; A. K. Islami (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2024)
Earthworms are one of the animals used as indicators to assess soil quality and fertility. In earthworm cultivation, several factors affect the life of earthworms, including temperature, pH, moisture, nutrient content, and media texture. This study aims to evaluate the productivity of earthworms (Lumbricus rubellus) in a mixed medium of cow manure and cricket manure. The method used in this study is a Completely Randomized Design (CRD) with 6 treatments and 3 replications, along with a Tukey posthoc test. The results showed that the addition of cricket manure to cow manure as a cultivation medium could increase earthworm productivity. The use of 90% cow manure with the addition of 10% cricket manure resulted in an average weight increase of 17 g, an average of 94 cocoons, and an average media reduction of 260.50 g. The addition of more than 10% cricket manure to cow manure could reduce earthworm productivity.